Design of Generating Dual Frequency Operation for Triangular Microstrip Antenna Using Electromagnetic Coupling - Surjati, Indra; Rahardjo, Eko Tjipto; Hartanto, Djoko (Makara Journal of Technology, 2005)
Design of Generating Dual Frequency Operation for Triangular Microstrip Antenna Using Electromagnetic Coupling. A new design is proposed in this paper by applying a pair of slits using a microstrip feed line. Therefore the microstrip line feeding system is electromagnetically coupled to the patch. The antenna works at two different frequencies in the range from 2 GHz to 4 GHz (S band frequency). The results of the simulation shows that the dual frequency operation can be created when the slit width is 1 mm and the height of the slits ranges from 10 mm to 14 mm with inter slit distance of 3 mm, 5 mm and 7 mm as well.